Fully Integrated Process Control. Issue 2 (April 2015) - Franz, Christoph; Ungers, Michael
Abstract Laser beam brazing and welding are well established joining techniques in the automotive industry; in particular for the body in white production. These processes are mainly used to join two‐piece trunk lids as well as to connect the roof and sidewall with a visible seam or to weld doors in steel or aluminum. Hence, the requirements upon the optical appearance of the brazed seams are very high and quality monitoring is essential. In cooperation of Scansonic MI GmbH and Fraunhofer ILT, a first prototype of a fully integrated on‐line process control system has been developed — SCeye.